The Dot Counting Test adds up: Validation and response pattern analysis in a mixed clinical veteran sample. Issue 4 (21st April 2018) - Soble, Jason R.; Santos, Octavio A.; Bain, Kathleen M.; Kirton, Joshua W.; Bailey, K. Chase; Critchfield, Edan A.; O'Rourke, Justin J. F.; Highsmith, Jonathan M.; González, David Andrés
ABSTRACT: Objective : This study cross-validated the Dot Counting Test (DCT) as a performance validity test (PVT) among a mixed clinical veteran sample. Completion time and error patterns also were examined by validity group and cognitive impairment status. Method : This cross-sectional study included 77 veterans who completed the DCT during clinical evaluation. Seventy-four percent ( N = 57) were classified as valid and 26% as noncredible ( N = 20) via the Word Memory Test (WMT) and Test of Memory Malingering (TOMM). Among valid participants, 47% ( N = 27) were cognitively impaired, and 53% ( N = 30) were unimpaired. Results : DCT performance was not significantly associated with age, education, or bilingualism. Seventy-five percent of the overall sample committed at least one error across the 12 stimulus cards; however, valid participants had a 27% higher rate of 0 errors, while noncredible participants had a 35% higher rate of ≥4 errors. Overall, noncredible individuals had significantly longer completion times, more errors, and higher E-scores. Conversely, those with cognitive impairment had longer completion times, but comparable errors to their unimpaired counterparts. Finally, DCT E-scores significantly predicted group membership with 83.1% classification accuracy and an area under the curve of .87 for identifying invalid performance. The optimal cut-score of 15 was associated with 70% sensitivity and 88% specificity. Conclusion : The DCT demonstrated good classification accuracy and sensitivity/specificity for identifying noncredible performance in this mixed clinical veteran sample, suggesting utility as a non-memory-based PVT with this population. Moreover, cognitive impairment significantly contributed to slower completion times, but not reduced accuracy.